Pyridine-containing ionic liquids lowly loaded in large mesoporous silica and their rapid CO2 gas adsorption at low partial pressure. (December 2019) - Xue, Chunfeng; Feng, Lin; Zhu, Hongye; Huang, Ruichao; Wang, Enyang; Du, Xiao; Liu, Gang; Hao, Xiaogang; Li, Kaixi
Graphical abstract: Ionic liquids with multiple active sites lowly immobilized in silica with large pore display swift adsorption, high capacity and good cyclic stability. Highlights: Two ionic liquids with multi active sites are made and loaded in large pore silica. It takes only 10 min for the ionogel NMS-15 to achieve saturation capacity at 50.0 °C. It takes 7.5 min for ionogel PMS-10 to achieve 90% CO2 saturation adsorption capacity. Its adsorption capacity retention is around 90% after 10 cycles adsorption test. Abstract: To achieve low cost, high rate and attractive capacity of CO2 adsorption by using ionic liquid (IL), tetrabutylammonium 2-hydroxypyridine ([N4444 ][2-Op]) and tetrabutylphosphonium 2-hydroxypyridine ([P4444][2-Op]) are newly prepared and immobilized into mesoporous silica (MS) with pore diameter of about 13.5 nm for fabricating mesostructured ionogel. It takes only 10.0 min for the ionogel NMS-15 (MS loaded with 15% IL [N4444 ][2-Op]) to achieve an adsorption capacity of 1.081 mmol CO2 /(g ionogel) (that is 1.10 mol CO2 /(mol IL)) at 50.0 °C and low CO2 partial pressure. Also, it only takes 7.5 min for the ionogel PMS-10 (MS loaded with 10% IL [P4444 ][2-Op]) to achieve 90% saturated adsorption capacity of 1.678 mmol CO2 /(g ionogel) (that is 3.72 mol CO2 /(mol IL)), which is 12.76 times higher than that of the pure IL [P4444 ][2-Op]. Its adsorption capacity retention is around 90% after performing 10 cycles continuous test. The results can be ascribed to the mesoporous silica with large pore that benefits to not only load more exposed IL but also remain necessary pathway for CO2 diffusion. Combining with low loading and cost, swift adsorption, high capacity as well as good cyclic and thermal stability make the ionogel PMS-10 a competitive candidate in CO2 capture from the flue gas.